No More Excuses: the shaping of community interventions in England and Wales in the 1980s. (1st January 2013) - Telford, Mark; Santatzoglou, Sotirios
In 1997, the UK Government signalled a sea-change in youth justice policy and practice with the publication of its tellingly titled White Paper No More Excuses . It laid the ground work for much of the current youth justice landscape in England and Wales. The White Paper provided not only a vision for the future of youth justice institutions, powers, and practices but also set out a disparaging narrative on the state of youth justice as it had developed, in particular, during the 1980s. The present paper, through an exploration of documentary materials and qualitative interviews with practitioners, challenges the historical account presented by the Government and offers a new narrative which explores a practice transition to a new youth justice specialism and the development of community interventions during the 1980s. It offers an insight into the practice logic of the period and thereby questions the 'legibility craft' of New Labour and the youth justice legacy it has left behind.